MANAGING TEACHERS' PEDAGOGICAL COMPETENCE DEVELOPMENT IN PUBLIC JUNIOR HIGH SCHOOLS - Yulce Hambali; Rudolf Kempa; Tanwey Gerson Ratumanan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the management of teachers' pedagogical competence development in public junior high schools in Baguala District, Ambon City. The study focuses on planning, implementation, evaluation, and supporting and inhibiting factors in three schools: SMP Negeri 9 Ambon, SMP Negeri 12 Ambon, and SMP Negeri 13 Ambon. A qualitative descriptive approach with a multisite case study design was used. Data were collected through in-depth interviews, non-participant observation, and documentation involving principals, vice principals for curriculum, and subject teachers. The data were analyzed through data condensation, data display, and conclusion drawing, while validity was strengthened through source, technique, and theoretical triangulation. The findings show that planning was generally systematic but differed across schools. SMP Negeri 9 Ambon emphasized school-based management planning through work meetings and curriculum programs; SMP Negeri 12 Ambon emphasized professional learning community planning through school-based MGMP and professional discussions; and SMP Negeri 13 Ambon emphasized reflective and evidence-based planning using academic supervision results. Implementation was carried out through workshops, MGMP activities, internal training on the Merdeka Curriculum, academic supervision, and technology-based learning media training. Evaluation was conducted through supervision, curriculum evaluation meetings, reflective discussions, and analysis of learning outcomes. The main supporting factors were principal support, active MGMP activities, teacher participation, and regular supervision, while the main obstacles were limited facilities, limited time, administrative workload, and training budget constraints. The study concludes that integrated managerial, collaborative, and reflective approaches are needed to strengthen sustainable pedagogical competence development.